Pendampingan Pemanfaatan Spreadsheet dan Looker Studio sebagai Buku Penghubung Digital di PAUD - Zein Hanni Pradana; Prasetyo Yuliantoro; Solichah Larasati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Communication between teachers and parents plays an important role in supporting early childhood education (ECE). However, at Hompimpaa Playschool, the communication medium used in the form of PDF-based liaison books has created several challenges, including time-consuming report preparation, static content, and difficulties in organizing and tracking children’s development records over time. This community service program aimed to assist the implementation of spreadsheets and Looker Studio as a more dynamic, efficient, and accessible digital liaison book. The program was conducted using a participatory mentoring and training approach through three face-to-face sessions, consisting of needs identification, core system training, and implementation assistance with evaluation. Teachers were guided to perform centralized data entry using spreadsheets, while parents were facilitated to monitor children’s development through a Looker Studio dashboard that can be filtered by date. The results indicate a shift in teachers’ workflow from preparing static PDF reports to a simpler and more structured data input process, as well as improved accessibility of information for parents without the need to repeatedly download report files. In addition, a practical user guide module was developed to support program sustainability. This activity demonstrates that the application of simple digital technologies, when accompanied by proper mentoring, can enhance teacher–parent communication, reduce teachers’ administrative workload, and has the potential to be replicated in other early childhood education institutions facing similar challenges.